ANALISIS PEMILIHAN KAPAL MILITER ADRI SEBAGAI ALINS/ALONGINS PUSDIKBEKANG PUSBEKANGAD GUNA MENINGKATKAN KOMPENTENSI HASIL DIDIK PENDIDIKAN PERWIRA ANGKUTAN AIR/TERMINAL - Sri Wisnu Wardono; Amin Lestari; Nurwahidin Nurwahidin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The aim of this research is to identify the criteria for selecting ADRI, determine alternatives in selecting ADRI and determine the best alternative for ADRI as Alins/Alongins Pusdikbekang Pusbekangad. This research approach is a type of qualitative method. The nature of this type of research is open research and exploration. Data sources consist of two types, namely, primary data sources and secondary data sources. The main instrument in this research is the researcher himself. Data collection techniques were carried out through observation, interviews and documentation studies. The data processing process is carried out using AHP and SWOT. The data analysis technique used is the AHP analysis technique. The research results obtained are: (a) Criteria for selecting ADRI as Alins/Alongins Pusdikbekang Pusbekangad. Based on interview data from resource persons, there are 3 types of KM ADRI that are considered in selecting ADRI as Alins/Alongins Pusdikbekang Pusbekangad. There are currently 4 KM ADRI with DWT 300, 3 KM ADRI with DWT 500 and 2 KM ADRI with DWT 1000 units. (b) Alternatives in selecting ADRI as Alins/Alongins for Pusdikbekang Pusbekangad education. The process of selecting ADRI as Alins/Alongins for Pusdikbekang Pusbekangad education goes through the stages in AHP theory. (c) The best alternative for ADRI as Alins/Alongins Pusdikbekang Pusbekangad is KM ADRI DWT 300 T.